2022
DOI: 10.1108/omj-09-2021-1355
|View full text |Cite
|
Sign up to set email alerts
|

CSR, moral licensing and organizational misconduct: a conceptual review

Abstract: Purpose The purpose of this paper is to conceptualize how past corporate social responsibility (CSR) affects the occurrence of organizational misconduct by the means of moral licensing. Design/methodology/approach To this end, the authors conduct a conceptual review and develop a framework illustrating how moral credits and moral credentials (moral licensing) may institutionalize irresponsibility and lead to subsequent misconduct. Findings The authors propose a conceptual framework that describes the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Based on the aim of this research, the model approach for the conceptual views proposed by Jaakkola (2020) will be adapted. The framework will illustrate how better outcomes (enhanced sustainability and performance) can be achieved through specific antecedents (SCCDCs and DCs) with logical causal linkages and mechanisms supported by empirical evidence and theoretical lenses (Bouzzine and Lueg, 2022). This will help in developing propositions that introduce new combinations of the relationships between these constructs in order to be empirically investigated in the future (Jaakkola, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the aim of this research, the model approach for the conceptual views proposed by Jaakkola (2020) will be adapted. The framework will illustrate how better outcomes (enhanced sustainability and performance) can be achieved through specific antecedents (SCCDCs and DCs) with logical causal linkages and mechanisms supported by empirical evidence and theoretical lenses (Bouzzine and Lueg, 2022). This will help in developing propositions that introduce new combinations of the relationships between these constructs in order to be empirically investigated in the future (Jaakkola, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Pressure from stakeholders such as investors, regulators, and the public causes firms to engage in environmental, social, and governance (ESG, hereafter) initiatives (Cicchiello et al, 2023). While such pressure can be argued to be a source for firms to engage in ESG activities, prior studies have found that the act can also be tied to morality and the ethical stand of the firm (Bouzzine, Lueg, 2023;Mitnick et al, 2023) or simply a strategic business move to gain economic benefits from the customers (Hamza, Jarboui, 2020;Herremans et al, 1993).…”
Section: Introductionmentioning
confidence: 99%